Microwave ablation assisted by three-dimensional visualization system as local therapy for relapsed hepatoblastoma: a small pilot study. - Cui, Rui; Yu, Jie; Gu, Ying; Cao, Feng; Liu, Feng-Yong; Dong, Li-Nan; Liang, Ping (Abdominal Radiology, 2019)
Purpose: We aimed to explore the feasibility of microwave ablation (MWA) assisted by three-dimensional visualization system for relapsed HB in children. Methods: From August 2014 to February 2017, five patients with relapsed HB were enrolled. A total of 12 liver tumors were treated with MWA assisted by a three-dimensional visualization system. Follow-up data were obtained in all patients. The residual liver volume, local tumor progression, new intrahepatic tumors, survival outcome, and complications were analyzed. Results: All tumors were completely ablated in a single session. The mean ablation time per tumor was 9.7 ± 8.6 min, and the median ablation/liver volume ratio was 2.37%. No local tumor progression was observed during a follow-up period of 9–39 months. All patients were still alive at the end of the follow-up. The median progression-free survival time after ablation was 9 months, and the median survival time after ablation was 12 months. No other complications were observed except for fever. Conclusions: MWA assisted by three-dimensional visualization system appears to be a safe and feasible local treatment for recurrent HB in pediatric patients.